2019
DOI: 10.1371/journal.pone.0209564
|View full text |Cite
|
Sign up to set email alerts
|

Multiple micronutrient status and predictors of anemia in young children aged 12-23 months living in New Delhi, India

Abstract: Anemia has been identified as a severe public health concern among young children in India, however, information on the prevalence of anemia attributed to micronutrient deficiencies is lacking. We aimed to assess multiple micronutrient status (iron, zinc, selenium, vitamin A, vitamin D, folate and vitamin B12) in young Indian children and to investigate the role of these seven micronutrients and other non-nutritional factors on hemoglobin concentrations and anemia. One-hundred and twenty children aged 12 to 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
1
12
1
3
Order By: Relevance
“…Moreover a study on children aged 12-23 months living in New Delhi found the majority to suffer from anemia (79.2%), of which 86%-93% was associated with iron deficiency. Iron status was reported as only nutritional factor being significantly inversely associated with anemia [89]. Equally, Hb levels of North Indian children were related to iron status, as well as folate and vitamin B12 status [67].…”
Section: Predictors Of Anemiamentioning
confidence: 98%
“…Moreover a study on children aged 12-23 months living in New Delhi found the majority to suffer from anemia (79.2%), of which 86%-93% was associated with iron deficiency. Iron status was reported as only nutritional factor being significantly inversely associated with anemia [89]. Equally, Hb levels of North Indian children were related to iron status, as well as folate and vitamin B12 status [67].…”
Section: Predictors Of Anemiamentioning
confidence: 98%
“…malaria) and inherited hemoglobin diseases [3]. Iron deficiency is a common cause of anemia in children and is associated with 86-93% of anemia in children [4]. Many observational studies indicate that the independent risk factors of anemia in children include preterm birth, low birth weight, and maternal anemia [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…9 Another study by Houghton et al evaluated 77 children of 12 to 23 months age-group and reported 29% deficiency of this nutrient. 10…”
Section: Introductionmentioning
confidence: 99%